Phonetic Transcription on Allomorphs of Past Participle Form of Regular Verbs - Ida Royani; Awliya Rahmi (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2019)
This research deals with the analysis of allomorphs of past participle form of the regular verb in English. Because allomorphs are phonologically conditioned, transcribing them becomes an interesting focus to figure out using phonetic transcription provided by IPA symbols and characters. It is not only in pronunciation accuracies, English language learners are also expected to be able to transcribe as they pronounce the words. Descriptive qualitative was used to study participants at fifth semester, English Education Majoring of IAIN Padangsidimpuan. They were randomly selected to provide data. Collecting data was established by interviewing and taking notes. The finding revealed that correct transcription occurred 69% of the total words and mostly appeared to the allomorph [id] such as [priventid], [kələktid], [dipəndid] and [lændid]. By dealing with responses, it was confirmed that a large number of participants argued to apply rule provided by morphophonemic context to get accurate transcription.